Lafoeina longitheca Jaderholm 1904 - Galea, Horia R. (Zenodo, 2007)
Lafoeina longitheca Jäderholm, 1904 (fig. 8O, P, table 5) Lafoeina longitheca Jäderholm, 1904b: 4; 1905: 20, figs 1–2, pl. 8; Billard, 1914: 12; Stepanjants, 1979: 41, pl. 7 fig. 9; Blanco et al. , 2000a: 269, fig. 2; Peña Cantero et al. , 2004: 2274, fig. 1A–B. Material examined . Stn. CFA — 14.iii.2006, 10– 30 m, S88: a sterile colony, epizoic on Bougainvillia pyramidata (MHNG INVE 53322). Type locality . Off South Georgia, West Antarctica. Description . Colony minute, stolonal, with individual hydrothecae and nematothecae arising directly from a branching, anastomosing hydrorhiza, firmly attached to its substrate, a colony of Bougainvillia pyramidata . Hydrothecae long, tubular, slightly curving, generally with 2–3 widely-spaced renovations; basal part narrowing fairly suddenly and attached directly to stolon; hydrothecal pedicel absent; hydrothecal rim slightly everted. Closing apparatus composed of several triangular flaps, connected by a hyaline membrane and folding together to form a pointed roof; sometimes operculum inwardly closed; with fine crease-line between bases of opercular flaps and hydrothecal rim. Nematothecae long, narrow, distal part slightly swollen, with small, circular, apical aperture; provided with several large, banana-shaped nematocysts. Remarks . Several authors reported a variable number of basal annulations of hydrothecae (Jäderholm 1904b, Stepanjants 1979, Blanco et al . 2000a). Peña Cantero et al. (2004) found only a few hydrothecae having a single annular constriction. In the present material, the majority of hydrothecae are smooth-walled, only a few of them being provided with 2–3 transverse constrictions of perisarc (fig. 8O). Renovations of hydrothecal margin were observed by Blanco et al. (2000a), but they were neither mentioned, nor figured, by Peña Cantero et al. (2004). Blanco et al. (2000a) reported hydranths with eight tentacles, while in the present material their number is ca 10. The gonothecae of this species still remain to be described. World distribution . Lafoeina ...